VULNERABILIDAD CONSTITUCIONAL DEL DERECHO A LA ESTABILIDAD LABORAL DE LOS SERVIDORES PÚBLICOS DEL ECUADOR, AL NO SER CONSULTADOS POR LA REFORMA ESTABLECIDA EN EL ART. 108 DEL REGLAMENTO DE LA LEY ORGÁNICA DEL SERVICIO PÚBLICO A TRAVÉS DEL DECRETO EJECUTIVO N° 813 - Correa Guamo, Dalton David (2015)
The state through its laws establishes verbatim the guarantees and the right to work possessed by citizens, whether in regard to public and private workers, however the development of this research focuses exclusively the work of officials that they are related directly with the state labor agency, such as the so-called public servants; that being forced to raise the compulsory resignation, is contradictory to the claims they enact constitutional laws, in view of the situation presented by this legal figure can represent therefore a condition for the income of workers who daily meet the needs of your family, being this as an arbitrary act contrary to the same constitutional mandate to guarantee the decent and sustainable jobs. This provision makes every year thousands of young officials who enter the public sector are forced to leave their jobs, or failing to be transferred to other work units. With regard to the first chapter called Concepts and General, is a chapter in which the salient terms of the problem is conceptualized, this in order to have a clear, accurate and concise about regarding the development understanding the present research work With regard to the second chapter called Source Labor Law, emphasis will be placed on the historical background of the work in all its forms, starting with the universal rise of the right to work, to the rise in our country as a right enshrined in the Constitution of the Republic. 6 With regard to the third chapter called The Labor Justice Public Service Workers, legal conceptualization and importance of the right to work in society, either as a form of self-improvement or collective improvement that is how society says. In the fourth chapter called Impact of the Implementation of Executive Order 813, reference is made to the impact they bring unemployment for integral and economic development of people, so the impact that entails buying waiver compensation and pension rights; likewise the legal nature and the fundamental characteristics of this action taken by the Executive; social, family and personal implications that entails a Standard Constitutional transgress; and finally the right to retire as a result of the arbitrary application of the purchase of waiver by state institutions. In Chapter V entitled Legal Aspects of Public Service, the legal elements of the right to have public employees will be analyzed, and a study of the Organic Law of the Public Service will also be made regarding the causes for the cessation of functions; Analysis of the Constitution of the Republic and finally legal analysis of Executive Order 813; It will make a brief analysis of comparative law with the laws of Spain, Venezuela and Mexico. In the sixth chapter Called Result Analysis and Verification, it has been directed to study this project field research, especially the views and opinions of professionals who are directly linked to this problem. Emphasis will be made to the conclusions and recommendations on the fundamental aspects of this problem, to which the possible solution of the problem is addressed by the Seventh approaches conclusive chapter; likewise it is proposed to the National Constituent Assembly reform that benefits the public's rights worker. This research work mainly analyzes the Executive Decree 813 issued by the Constitutional President Rafael Correa Delgado, based on the powers granted under the Nral. 13 Article 147 of the Constitution of the Republic; together with the implications and contradictions that are generated in this important study, an important branch of public law, contemplating the reality of civil servants and the importance of their work as a key cog in the development of our administrative system. Added to this the purchase of resignation without having reached the retirement that everyone belonging to this nation is on the right of yearning aim of better days.